(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
A 55-year-old male presented with complete left-sided weakness of the body with a National Institutes of Health Stroke Scale (NIHSS) 15 and Alberta Stroke Program Early Computed Tomography (ASPECT) score 8 and occlusion of the right middle cerebral artery (MCA) in the M1 segment on Computed Tomography Angiography (CTA). Intravenous thrombolysis (IVT) was not performed as symptoms developed at sleep. Mechanical Thrombectomy was performed after 4.5 hours of the symptom onset with recanalization of Thrombolysis in Cerebral Infarction (TICI classification 2b). Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 90-94